Effects of neurofeedback on the dysregulation profile in children with ADHD: SCP NF meets SDQ-DP – a retrospective analysis. Issue 2 (24th January 2020) - Heinrich, Hartmut; Gevensleben, Holger; Becker, Andreas; Rothenberger, Aribert
Abstract: Background: As children with attention-deficit/hyperactivity disorder (ADHD) usually show psychopathological signs beyond their core symptoms (e.g. elevated scores of the dysregulation profile (DP) in 30–40%), treatments with a broader approach to self-regulation skills may be supportive. Neurofeedback (NF) may reflect such an option. Aim of the present analysis was to compare the effects of slow cortical potential (SCP) NF and θ / β NF on the DP using data from a previous trial. Methods: Thirty children with ADHD (aged 8–12 years) and a DP score in the Strengths and Difficulties Questionnaire (SDQ-DP) ⩾ 3 were included. NF treatment consisted of one block of SCP NF and one block of θ / β NF (18 units per block) allowing an intraindividual comparison. Effects of the NF protocols were also contrasted to a control group ( n = 18) that completed an attention skills training (between-group analysis). Results: Regarding the SDQ-DP, SCP NF was superior to θ / β NF and the control condition. Effects of SCP NF and θ / β NF on ADHD symptom severity were not significantly different. The SDQ-DP score did not correlate with EEG-related measures previously found to be predictors for SCP NF on ADHD symptoms. Conclusions: SCP NF may reflect a more general approach to improve cognitive, emotional and behavioral self-regulation skills. If confirmed in a larger sample, the SDQ-DP score could be used as an indication criterion and contribute to the individualization of NF in ADHD. Overall, the differential effect provides further evidence for the specificity of NF effects.